Integrated Metabolomics and Transcriptome Analyses Unveil Pathways Involved in Sugar Content and Rind Color of Two Sugarcane Varieties - Yuan, Zhaonian; Dong, Fei; Pang, Ziqin; Fallah, Nyumah; Zhou, Yongmei; Li, Zhi; Hu, Chaohua (Frontiers in Plant Science, 2022)
Metabolic composition can have potential impact on several vital agronomic traits, and metabolomics, which represents the bioactive compounds in plant tissues, is widely considered as a powerful approach for linking phenotype–genotype interactions. However, metabolites related to cane traits such as sugar content, rind color, and texture differences in different sugarcane cultivars using metabolome integrated with transcriptome remain largely inconclusive. In this study, metabolome integrated with transcriptome analyses were performed to identify and quantify metabolites composition, and have better insight into the molecular mechanisms underpinning the different cane traits, namely, brix, rind color, and textures in the stems (S) and leaves (L) of sugarcane varieties FN41 and 165402. We also identified metabolites and associated genes in the phenylpropanoid and flavonoid biosynthesis pathways, starch and sucrose metabolism. A total of 512 metabolites from 11 classes, with the vast majority (122) belonging to flavonoids were identified. Moreover, the relatively high amount of D-fructose 6-p, D-glucose6-p and glucose1-p detected in FN41L may have been transported and distributed by source and sink of the cane, and a majority of them reached the stem of sugarcane FN41L, thereby promoting the high accumulation of sugar in FN41S. Observations also revealed that genes such as C4H, CHS, F3H, F3’H, DFR, and FG2 in phenylpropanoid and flavonoid biosynthesis pathways were the major factors impacting the rind color and contrasting texture of FN41 and 165204. Further analysis revealed that weighted gene co-expression network analysis (WGCNA) hub genes and six transcription factors, namely, Tify and NAC, MYB-related, C2C2-Dof, WRKY, and bHLH play a key role in phenylpropanoid biosynthesis, flavone and flavonol biosynthesis, starch and sucrose metabolism. Additionally, metabolites such as L-phenylalanine, tyrosine, sinapaldehyde, pinobanksin, kaempferin, and nictoflorin were the potential drivers of phenotypic differences. Our finding also demonstrated that genes and metabolites in the starch and sucrose metabolism had a significant effect on cane sugar content. Overall, this study provided valuable insight into the molecular mechanisms underpinning high sugar accumulation and rind color in sugarcane, which we believe is important for future sugarcane breeding programs and the selection of high biomass varieties.